Importance of Beam Analysis for Industry 4.0: Ensuring the quality of welding and cutting by constantly monitoring the laser parameters. Issue 4 (1st August 2019) - Stumpp, Barbara
Abstract: The laser revolutionized production. Compared to resistance spot welding, the machining speed has been increased by more than 50 % and it allows new joining and construction concepts. But whether car body parts are welded or turbine blades are repaired by laser powder cladding, both require the highest process quality and thus optimal adjustment of the laser parameters. From this point of view, the use of laser diagnostic systems, such as the PowerMeasuringModule and the FocusParameterMonitor from Primes, is worthwhile.